Analysis of steel highway bridges by line-girder and exact calculation methods - Ülker, F.; İnce, R. (My University, 2018)
A three-span steel bridge is analyzed in this research with Line-Girder and SAP2000 program. With the LineGirder method, analysis, calculations and design have been seen to be quite complex, tedious and timeconsuming, with conclusions that are uncertain. It has been demonstrated in this study that the analysis isdone effectively in a short period of time by using precise calculation methods instead of this method andthe appropriate results are achieved.
Keywords: İnşaat Mühendisliği